The Influence of Digital Transformation, Knowledge Management Practices, and Market Orientation on Business Performance in the Retail Industry - Apriani Riyanti; Tyahya Whisnu Hendratni; Jefriyanto; Isna Juwita; Anita Bawaiqki Wandanaya; Pas Mahyu Akhirianto (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study's main purpose is to evaluate how digital transformation, knowledge management practices, and market orientation interact, thereby affecting productivity in the retail industry of Indonesia. The researchers that the rivalries in the retail sector may lead to the question that the companies would be forced to respond technology-wise and market-wise almost instantly to the customer's behavior, in this instance, the customers and marketing strategies changes. The research adopts a quantitative method for collecting data from 150 participants who include operational staff, supervisors, and managers of retailers where digital systems have been installed. The investigators applied the purposive sampling method with the work experience and involvement in the company's digitalization as the criteria. The questionnaire items were subjected to validation for item-total validity plus reliability through Cronbach's Alpha and thereafter went through classical assumptions such as normality, multicollinearity, and heteroscedasticity before being further analyzed by multiple linear regression. The findings show that the performance of retail business is positively and significantly influenced by all three independent variables. The present research, from the theoretical standpoint, contributes to the understanding of retail strategic management and digital transformation in the literature. Moreover, it also paves the way for practice by suggesting that retail firms gradually adopt technology, engage in knowledge management, and improve their market orientation in order to achieve and sustain high business performance.